Pengaruh Pemanfaatan PET pada Laston Lapis Pengikat Terhadap Parameter Marshall - Prameswari, Putri Ajeng; Pratomo, Priyo; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Utilization of plastic waste can be used as an ingredient added to the binder layer of asphaltconcrete (AC-BC). The purpose of this study was to determine the characteristics of the Marshallparameters due to the addition of PET (Polyethylene Terephthalate) in the binder layer of asphaltconcrete (AC-BC) using the method of Marshall and refer to the specifications of Highways, 2010.The research was carried out by adding pieces of PET in the asphalt mix using the dry method.Before adding PET to the asphalt mixture, first making a specimen of middle limit gradation andupper limit gradation. The value of Optimum Asphalt Content (KAO) obtained in the two groupsof test object is equal to 6.44%. Furthermore, the addition of PET in the asphalt mix on the KAOvalue. PET levels are added to the mixture which is 2%, 4%, 6%, 8%, and 10% of the weight ofthe asphalt. From the results of the testing and analysis of Marshall, the addition of PET onasphalt concrete binder layer can increase the value of stability. The most of stability value is onthe addition of 2% PET. Value stability due to the addition of PET in the asphalt mix increasedcompared to asphalt mixture without PET. Levels of PET good addition to the asphalt mixture thatis 2% because in addition to high stability values, parameters such as VIM Marshall, VFA, VMA,MQ and Flow also has qualified specification of Highways, 2010.Keywords: AC-BC, PET, stability, Marshall parameter, specification of Highways 2010